Programmable One-pot Synthesis of Heparin Pentasaccharide Fondaparinux - Dey, Supriya (Org Lett, 2020)
The clinically approved Fondaparinux (Arixtra) has been used for the treatment of deep vein thrombosis (DVT) and acute pulmonary embolism (PE) since 2002, and considered to be better than the low molecular-weight heparin (LMWH) in terms of anticoagulation response, duration of action and biosafety. However, the synthetic methods developed for its manufacture in the past years are relatively complicated thus restricting its extensive use. We reported here a potentially scalable and programmable one-pot synthesis of Fondaparinux using the [1,2,2] strategy and designed thioglycosides with well-defined reactivity as building blocks.